1987
DOI: 10.1021/bi00394a016
|View full text |Cite
|
Sign up to set email alerts
|

cDNA sequence coding for a rat glia-derived nexin and its homology to members of the serpin superfamily

Abstract: Rat glial cells release a neurite-promoting factor with serine protease inhibitory activity. By using a rat glioma cDNA clone as a probe, it was possible to isolate rat cDNAs containing the entire sequence coding for this neurite-promoting factor. The largest rat cDNA (approximately 2100 bp) was characterized by DNA sequencing. It contained the entire coding region, 135 bp of the 5' nontranslated region, and about 750 bp of the 3' nontranslated region. The open reading frame coded for 397 amino acids including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 27 publications
0
93
0
Order By: Relevance
“…To obtain a cRNA probe for mouse PN-I, a 328 bp PstI fragment of a rat PN-I cDNA (Sommer et al, 1987) was subcloned in pGEMI. The plasmid was linearized with EcoRI and transcribed with SP6 RNA polymerase (Busso et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain a cRNA probe for mouse PN-I, a 328 bp PstI fragment of a rat PN-I cDNA (Sommer et al, 1987) was subcloned in pGEMI. The plasmid was linearized with EcoRI and transcribed with SP6 RNA polymerase (Busso et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Using radiolabelled uPA, we have detected high levels of a uPA ligand in extracts of adult mouse and rat seminal vesicles. We have identified this ligand as protease nexin I (PN-I), a serpin released by human fibroblasts (Baker et al, 1980) and identical to glia-derived nexin (GDN) (Gloor et al, 1986;Sommer et al, 1987;McGrogan et al, 1988), first detected as a factor promoting neurite outgrowth in vitro (Guenther et al, 1985) that is found in different structures of the nervous system (Reinhard et al, 1988;Meier et al, 1989). PN-I reacts with and inhibits thrombin, uPA, tissuetype PA (tPA), trypsin and plasmin (Baker et al, 1980;Eaton and Baker, 1983;Guenther et al, 1985;Stone et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…This cassette was generated originally by deleting a DNA fragment (from the BanI site in exon 2, upstream of the translation start codon, to a XhoI site in exon 4) and inserting an XhoI linker. A blunted HindIII-EcoRI DNA fragment containing the rat PN-1 cDNA (Sommer et al, 1987) was inserted into the blunted XhoI site of the Thy 1 cassette. The PN-1 cDNA encompasses the authentic PN-1 translation initiation (ATG) codon, signal peptide, and termination codon (TGA).…”
Section: Methodsmentioning
confidence: 99%
“…Northern blots were hybridized to random-primed 32 P-labeled DNA probes. The following probes were used: a 750 bp XhoI-BamHI DNA fragment from exon 4 of the mouse Thy 1.2 gene (Ingraham et al, 1986) and a 1351 bp XhoI-XbaI DNA fragment carrying the rat PN-1 cDNA (Gloor et al, 1986;Sommer et al, 1987). For the thrombin inhibition assay, a previously described method (Nick et al, 1990) was adapted to microtiter plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation